Operationalizing Political Analysis : The Expected Utility Stakeholder Model and Governance Reforms - Nunberg, Barbara (World Bank, Washington, DC, 2012)
Changes in public sector institutions and governance systems in developing countries may be relatively easy to achieve technically, but very tough to implement politically. Such reforms create winners and losers, so understanding the political realities that shape the incentives of key stakeholders in a given program or policy is vital to securing consensus-and may mean the difference between a well-designed intervention that mobilizes critical support and a failed initiative that alienates crucial clients.